catena-Poly[[bis(nitrato-κO)cadmium]bis[μ-1,4-bis(pyridin-3-ylmethoxy)benzene-κ(2) N:N′]] - Zhang, Shuang (International Union of Crystallography, 2011)
In the title compound, [Cd(NO(3))(2)(C(18)H(16)N(2)O(2))(2)](n), the six-coordinated Cd(II) ion is located on an inversion center and has a distorted octahedral environment defined by four N atoms from four 1,4-bis(pyridin-3-ylmethoxy)benzene ligands and two O atoms from two nitrate anions. The ligands link the Cd(II) ions into a ribbon-like structure running along [201]. One O atom of the nitrate anion is disordered over two positions with site-occupancy factors of 0.59 (2) and 0.41 (2).